Public response to the appearance of ecological landscape design : A case study of Chulalongkorn University Centenary Park - Wilasinee Suksawang (Chulalongkorn University, 2020)
The appearance of ecological landscape design often causes public dissatisfaction. Precedent texts and studies, especially in the landscape perception and design fields, reiterated the affection for the ‘picturesque’ and the ‘park-like’ landscape of most Americans, resulting in their resistance to the ‘messiness’ of ecological landscapes. This research, therefore, studied how Thais perceive and respond to the look of the landscape, investigating if the ‘picturesque’ and the ‘messiness’ play a role in their perception and appreciation of ecological urban park design in the country. The questionnaires were distributed to gather respondents’ notions of beautiful, natural, and ecologically sustainable landscapes as well as opinions on the ecological landscape design of Chulalongkorn University Centenary Park-a pioneer and epitome of ecological landscape design in Bangkok. Four groups of respondents included park users, affiliates of Chulalongkorn University, Bangkok residents, and landscape professionals. The analysis of 315 responses reveals the attachment to the ‘picturesque’ ideal and the ‘park-like’ landscape, as well as the disinclination for the ‘messiness’ and poor maintenance of most Thais. Also, the ‘picturesque’ conventions, ‘cues to care’ tactic, familiarity, and knowledge about nature and ecology seemed to involve in their perception of beautiful, natural, and ecologically sustainable landscapes. Based on these findings, the research suggests strategies for designing ecological urban public parks in Bangkok in order to achieve not only ecological function, but also aesthetic expression, with the ultimate goal of achieving public positive attitude toward, and widespread support for the ecological landscape projects in the city.